STUDY ON SIMULATION OF CHAIN DRIVE’DYNAMIC BEHAVIOR BASED ON RECURDYN - TAO DongBo; HE Chao; FAN XinBo; TUO QianJin (Jixie qiangdu)
Chain drive is a convenient mechanical transmission for use,which has such characteristics as compact structure and high reliability.Chain is a flexible body.In the course of transmission,the polygon effect and the meshing impact are the fundamental reason to produce dynamic loadand vibration,meanwhile,this process is abstract and difficult to be understood.With chain drive kinematic theory and multi-rigid-body dynamics as the theoretical basis,the polygon effect and the meshing impact were simulatedby using Recur Dyn software,which visually showedthe inhomogeneity of the chain speedand the beating effect of the chain drive.It provides the right virtual prototyping model for the whole machine simulation and mechanism optimization analysis about chain transmission,and it has some guidance and reference value for the development and improvement of products about chain drive.